Disambiguation of ambiguous figures in the brain - Ishizu, Tomohiro (Frontiers in Human Neuroscience, 2013)
Disambiguation refers to the ability to interpret ambiguous information in a sensible way, which is important in an ever-changing external environment. Disambiguation occurs when prior knowledge is given before an ambiguous stimulus is presented. For example, labeling a series of meaningless blobs as a “human body” can change the observer's perception. The aim of this experiment was to study the neural circuitry underlying disambiguation caused by prior knowledge. We presented to participants a series of meaningless blobs with different contextual information. As participants performed this task, we used magnetoencephalography to map the brain areas that were activated when participants perceived blobs as a human body. The participants were presented identical sets of blob stimuli, and were instructed that a human body would appear more frequently in the “high body” condition than in the “low body” condition. We found the blob stimuli were more frequently perceived as the human body when they were presented in the “high body” condition. Such contextual modulation correlated with activity in the extrastriate body area (EBA) and the inferior frontal gyrus (IFG). Furthermore, we observed that IFG activation preceded EBA activation. These findings suggest that top-down processing in the IFG plays a role in disambiguating ambiguous information and modifying an individual's perceptions.